Blended Learning Reimagined: Teaching and Learning in Challenging Contexts - Shanti Divaharan; Alexius Chia (MDPI AG, 2022)
The COVID-19 global pandemic has caused disruptions around the world with devastating consequences socially and economically. Education was not spared. Schools and institutions of higher learning (IHLs) had to grapple with new sets of demands. With most countries forced into lockdown to stem the spread of the virus, some turned to technology-mediated learning to provide some kind continuity for learning to still take place. This concept paper will share some of the key learning points and strategies culled from experiences having to pivot almost overnight to embracing technology and new learning environments, which were sometimes remote or neglected in a milieu and culture that often prided itself in effective physical face-to-face interactions. This article will then draw upon how the Blended Learning approach, undergirded by Connectivism, was implemented in a local IHL. Examples of the different types of blended learning designs that were employed will be described alongside examples on how educators can distinguish between them to engage their learners in both modes.